2018
DOI: 10.1016/j.neuroimage.2018.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Differences in steady-state glutamate levels and variability between ‘non-task-active’ conditions: Evidence from 1H fMRS of the prefrontal cortex

Abstract: Proton functional magnetic resonance spectroscopy (H fMRS) is a noninvasive neuroimaging technique capable of detecting dynamic changes in glutamate related to task-related demands at a temporal resolution under 1 min. Several recent H fMRS studies demonstrated elevated steady-state levels of glutamate of 2% or greater during different 'task-active' conditions, relative to a 'non-task-active' control condition. However, the 'control' condition from these studies does vary with respect to the degree of constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…The variance minimization phase consisted of a flashing grayscale checkerboard (centered on-screen; 3Hz) presented for 208s. Previous research in our laboratory demonstrated that the flashing checkerboard minimized glutamate variance better than alternative approaches ( 36 ). The working memory task consisted of seven interleaved repetitions of passive visual fixation [32s; 2s of instructions (“Rest”), 30s of static fixation cross centered on-screen] and letter 2-back [64s; 4s of instructions (“2-back”), 20 capitalized letters presented serially 3s/letter (60s total); each letter was presented on screen for 500ms followed by 2,500ms of blank screen].…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…The variance minimization phase consisted of a flashing grayscale checkerboard (centered on-screen; 3Hz) presented for 208s. Previous research in our laboratory demonstrated that the flashing checkerboard minimized glutamate variance better than alternative approaches ( 36 ). The working memory task consisted of seven interleaved repetitions of passive visual fixation [32s; 2s of instructions (“Rest”), 30s of static fixation cross centered on-screen] and letter 2-back [64s; 4s of instructions (“2-back”), 20 capitalized letters presented serially 3s/letter (60s total); each letter was presented on screen for 500ms followed by 2,500ms of blank screen].…”
Section: Methodsmentioning
confidence: 90%
“…1 H fMRS is a neuroimaging technique that facilitates direct measurement of dynamic neurochemistry levels. Seminal 1 H fMRS research was conducted at high field, but technological advances have made detection of glutamate modulation possible at 3T ( 9 , 15 , 36 ). The 1 H fMRS signal does not differentiate cell type, neuron vs. glia, or compartment, intracellular vs. extracellular, but is directly proportional to the concentration of molecules within the voxel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of errors seen in the schizophrenia group for the 0-back condition suggests this was challenging for some participants and glutamatergic measures may have already increased from a resting condition level, preventing changes between the 0-back and 2-back conditions from being detected. Recent work has noted the importance of the 'non-task-active' behavioural paradigm in 1 H-fMRS studies and suggests a continuous visual fixation cross exhibits less variability and lower levels of glutamate and therefore providing a better approximation of baseline state than other behavioural paradigms including eyes closed, flashing checkerboard or finger tapping (Lynn et al, 2018). An alternative explanation for the worse performance in the schizophrenia group that should also be considered is that of aberrant salience (Kapur, 2003), whereby these patients may be more likely to be inappropriately processing stimuli in their environment that would normally be considered irrelevant, and as a result might be less able/or willing to engage with and focus attention to the task in question.…”
Section: Limitationsmentioning
confidence: 99%